PARTISIPASI PENDIDIKAN MASYARAKAT PEDESAAN DAN TRADISI PERNIKAHAN USIA DINI DI INDONESIA - Waskito, Waskito (Jurnal Sejarah dan Budaya, 2010)
Abstract. Two main problems in Indonesian many rural areas are the low participation of education and early marriage tradition. So, the study about relation between educational participation and early marriage tradition has a strategical meaning for development in Indonesia. There are several factors involved in these two problems. Every rural has different factors So, it is need to be formulated a comprehensive and contextual model to solve those problems.